EFFECT OF H-1 ANTIHISTAMINE PROMETHAZINE ONFERTILITY IN MALE ALBINO RATS. - DR. GAJANAN PURUSHOTTAM KULKARNI; DR. YOGITA LAXMIKANT KULKARNI; DR. PADMANABHA T. S.; DR. MOHAMMED MATEENUDDIN (International Journal of Pharma and Bio Sciences, 2013)
Present study was undertaken to evaluate effects of Promethazine, a commonly used H1 Histamine antagonist on fertility in adult Male Albino rats. Although there are evidences of histaminergic system in the testis and spermicidal action of H1 receptor antagonists in vitro, there is complete lack of information about its effects on sperm count, sperm motility and histopathology of testes in vivo(1). Male albino rats were segregated in 4 groups of 24 animals each. Group 1 received Promethazine 6 mg / Kg / day orally daily for two weeks period, group II received Promethazine 6 mg / Kg orally for six weeks, group III and IV which received 2ml normal saline daily orally for two and six weeks respectively served as control. Twenty four hours after the last treatment animals were anesthetized and laparotomy was conducted. Epididymis removed & minced in 1ml phosphate buffer solution (PBS PH 7.2) and epdidymal sperms were studied for sperm count and sperm motility. Sperm count was done using neubars chamer and sperm motility was studied after staining with 1% acqueous eosin(2),(9). Histopathology of testes was done after scarification of rats. Data were analysed using Mann whitney ‘U’ Test. Sperm count and sperm motility in Promethazine treated groups was significantly reduced, as compared to control groups. Promethazine reduced sperm count by interfering spermatogenesis and decreased motility, probably affecting intracellular Ca+concentration. Hemorrhage and necrosis of seminiferous tubules was seen in histopathology of promethazine treated rats. But more studies are necessary to reveal exact mechanism of action.